Rancangan Pembelajaran Berkarakteristik Pembelajaran Inovatif Abad 21 pada Materi Perdagangan Internasional dengan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Berfikir Kritis Siswa di SMP Negeri 5 Adiwerna - Roisah (Cakrawala: Jurnal Pendidikan, 2022)
This article presents how the Problem-Based Learning model is applied to International Trade material in class IX of SMP Negeri 5 Adiwerna. Learning Model Problem Based Learning (PBL) or Problem-Based Learning is a learning approach that uses real-world problems as a context for students to learn about critical thinking and problem-solving skills, as well as to acquire essential knowledge and concepts from the subject matter. Problem-based learning is used to stimulate higher-order thinking in problem-oriented situations, including learning. The steps of the learning model have 5 stages, namely: 1) The stage of student orientation to problems, 2) Stage of organizing students in learning, 3) Stage of guiding investigations individually or in groups, 4) The stage of developing and presenting the results of the work, 5) The stage of analyzing and evaluating the problem solving process. Furthermore, how the activities of teachers and students in the Problem Based Learning model in the number pattern material will be discussed in this article